Scholarship Models Around the Globe - Embracing Diversity, New Trends and Opportunities - Justino, E.; Casquilho-Martins, I. (2025)
Scholarship Models Around the Globe – Embracing Diversity, New Trends and Opportunities offers a comprehensive exploration of global higher education funding systems and their impact on students' academic journeys and career trajectories. With a focus on equity, inclusion, and the challenges faced by historically marginalized groups, this volume provides insights into diverse scholarship models across different regions. By examining the interplay between financial support and access to higher education, the book highlights both the successes and limitations of various funding initiatives. It explores social mobility, fosters sustainable development, and addresses systemic inequalities while offering policy recommendations for more inclusive and effective programmes. Engaging with comparative case studies from Africa, Latin America, the Middle East, and beyond, this volume is an essential resource for researchers, educators, and policymakers seeking to understand the evolving dynamics of higher education funding. Rich with diverse perspectives, this book highlights emerging trends and innovative practices, making it an essential part of the ongoing conversation on educational equity and the future of global scholarship programs.